Role of Changes in SARS-CoV-2 Spike Protein and its Human Interaction and Nutritional Impact and Dental and Health Hygiene - Tarig Ginawi; Fehaid Muqbil Alshammari; Ibtihag Siddig Elnaem Mohamed-Nour; Rania Abdeen Husin Abdalla; Abeer, Hassan Elhaj; Gamal Eldin Mohammed Osman Elhussein; Firas S. Azzeh; Amal Dhar; Ahmed Fathy Abdou Abbas; Fahmida Khatoon; et al. (Current Innovations in Disease and Health Research Vol. 8, 2023)
Nutrition is pivotal in supporting the immune system. Immune homeostasis is indeed well-regulated by a balanced nutrition. It is key in the defense against viral threats. The world has been in a state of a pandemic for more than a year, humanity is suffering great losses. Millions of people have died, and countries have been in proper lockdowns to stay safe which has led to the greater economic and social loss. The virus that turned the world over is referred to as the sars COV 2 virus commonly known as the coronavirus. Aim of this review is to the aim of this study was to determine the mutation(s) in the sequence of the spike protein of the SARS-CoV-2 that might be favoring human to human transmission and to determine nutritional role.